Cornish churches in the nineteenth century the church notes of the Lysons brothers and Sir Stephen Glynne - Lysons, Daniel 1762-1834; Lysons, Samuel 1763-1819; Glynne, Stephen Richard 1807-1874 (Devon & Cornwall Record Society, 2024)
"These two sets of little-known notes, recorded first-hand by 19th-century antiquaries, underpin our understanding of how these structures developed into the buildings we see today. These manuscript notes on Cornish churches contain much previously unknown material, and were compiled by three 19th century antiquaries. The brothers Daniel and Samuel Lysons toured the county from 1805-11, working towards the publication of the Cornish volume of their series Magna Britannia. Sir Stephen Glynne, 9th Bt of Hawarden, had a passion for recording church architecture, travelling widely around the UK and the continent. Presented here for the first time, the two sets of notes neatly complement each other, the Lysons' focusing on notable features in the churches, while Glynne's form clear architectonic descriptions. An Introduction uncovers the working methods of these men, and their roles in understanding architectural descriptions and ecclesiology. The text is also supplemented by further archival research which shows how these structures have evolved between the nineteenth century and today."
Keywords: Geschichte 1803-1900; Kirche; Architektur; Cornwall; Quelle